Hubungan Gaya Hidup dengan Insiden Fibroadenoma - Nur Syifa Fara Wahida Purba; Iqbal Pahlevi Adeputra Nasution; Quranayati (Pusat Riset dan Inovasi Nasional, 2025)
Fibroadenoma mammae is one of the most common benign solid lump with a prevalence of 15-23% based on autopsy study. Characteristics of Fibroadenoma mammae (FAM) is a firm mass with sharply circumscribed and the diameter is no more than 3 cm.Fibroadenoma is typically occurring in patients between the ages of 14 and 35 years, but it can happen at any age. The risk factors of fibroadenoma and breast cancer are similar. The highest risk factors of benign breast lump are environment and lifestyle. This study aimed to observe the correlation between lifestyles and the incidence of fibroadenoma. The lifestyles under this study are dietary patterns, physical activity, alcohol consumption, and smoking. An analytical observational study with cross-sectional design is used to perform fibroadenoma patients who were under primary care at the University of Sumatera Utara Hospital year 2021-2022. A chi square test was used to analyze the data with p value ≤0,05. The test showed p-value of the lifestyles; 0,032 for dietary pattern, 0,031 for physical activity, 0,334 for smoking, and none for alcohol consumption. The p value of alcohol consumption was not found due to no respondents drink alcohol. Dietary pattern and physical activity are associated with incidence of fibroadenoma. Smoking and alcohol consumption are not associated with incidence of fibroadenoma.